9(2+2)-4w=3w-10

Simple and best practice solution for 9(2+2)-4w=3w-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2+2)-4w=3w-10 equation:


Simplifying
9(2 + 2) + -4w = 3w + -10

Combine like terms: 2 + 2 = 4
9(4) + -4w = 3w + -10

Multiply 9 * 4
36 + -4w = 3w + -10

Reorder the terms:
36 + -4w = -10 + 3w

Solving
36 + -4w = -10 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
36 + -4w + -3w = -10 + 3w + -3w

Combine like terms: -4w + -3w = -7w
36 + -7w = -10 + 3w + -3w

Combine like terms: 3w + -3w = 0
36 + -7w = -10 + 0
36 + -7w = -10

Add '-36' to each side of the equation.
36 + -36 + -7w = -10 + -36

Combine like terms: 36 + -36 = 0
0 + -7w = -10 + -36
-7w = -10 + -36

Combine like terms: -10 + -36 = -46
-7w = -46

Divide each side by '-7'.
w = 6.571428571

Simplifying
w = 6.571428571

See similar equations:

| 7x+4-2x=49 | | 24=-4(-y+3) | | 6x+x=3(2-x) | | (x+5)=(x-6) | | 6(t-2)-76=142 | | 78x+3x=81 | | 6(t+2)-76=142 | | 8b+4b-24=12 | | 5(p+3)-6=7p+9 | | x^4+96=22x^2 | | 8(wx-v)=5(x+v) | | 1.5+0.5x=2.65 | | 2x-3-5x=13+4x-2 | | 9a^2-12a+4=0 | | 5(-x+2)=-15 | | -5x-2(-5x-18)=-24 | | 6(3x+4)+5(2x-1)= | | ax+5=4x+b | | (x+4)/(3-5)=-(2/5) | | -5x-2(-5x-18)=24 | | 5x+10=-19 | | 24-6= | | 3(x+2)=2(2x-7)+9 | | (6-x)/(3-2)=(1/2) | | 82=2x+7x-8 | | d+27= | | 49t^2-36=0 | | 50-x-15=15 | | 5x+5=-2x+12 | | 4x-5+2=(2x+1) | | 14=2(3+4x)-8 | | 4(x+3)=3(3x-7) |

Equations solver categories